2018
DOI: 10.5812/intjssh.84349
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Mawashi-Geri in Technique in Karate: Review Article

Abstract: Mawashi-Geri Jodan technique (circular kicking to the opponent's head), is one of the most commonly used techniquesin the Karate, especially in the combat style. Although the speed of the implementation of the technique plays an important role in gaining points, there is no specific pattern for optimal performance of the technique. In this research, it was aimed at reviewing the results of the previous research that has been conducted on the effective issues relating to the success of this technique performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…The examined VL and VM muscles are extensors in the knee joint [ 46 ], while the RF is an extensor in the knee and also a flexor in the hip joint [ 47 ]. Specifically, the RF muscle performs both of these actions during a kick by increasing the speed of the knee and reducing the time of lifting the foot up from the ground [ 13 , 48 ]. Since both hip flexion (jap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The examined VL and VM muscles are extensors in the knee joint [ 46 ], while the RF is an extensor in the knee and also a flexor in the hip joint [ 47 ]. Specifically, the RF muscle performs both of these actions during a kick by increasing the speed of the knee and reducing the time of lifting the foot up from the ground [ 13 , 48 ]. Since both hip flexion (jap.…”
Section: Discussionmentioning
confidence: 99%
“…Karate punches, kicks, blocks and frequent movements require a joint action sequence with the participation of the leg, pelvis, torso and arm muscles. Hariri et al [ 13 ] highlighted the importance of leg muscle properties in two cases in karate sport. One is regarding kicks, where they pointed out that increasing the knee speed and minimizing the time elapsed from the ground is effective in improving kicking techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The balance training of CT protocol focuses on multiple abilities of balance and stability including the posterior thigh muscles, the abdominal muscles, and the hip muscles, especially improving the stability of ankle during the process of landing and take-off ( Hewett et al, 2010 ). Hariri and Sadeghi (2018) found that it was necessary to increase the speed of the knee in order to achieve maximum foot speed toward the target in the performance of the Karate. Improving muscle performance and joint movement is thus of great importance in quick movement during badminton matches, especially in enhancing knee function.…”
Section: Discussionmentioning
confidence: 99%
“…Karate [74] is a popular martial art, invited at the Tokyo Olympics, and thus, there have been efforts in applying new technologies to its modeling from a computing perspective to improve psychomotor performance. In this sense, [75] has reviewed the technologies used in twelve articles to analyze the "mawasi geri" (side kick) technique, finding that several kinds of inputs, such as 3D video image, inertial sensors (accelerometers, gyroscopes, magnetometers) and EMG sensors can be used to study the speed, position, movements of body parts, working muscles, etc. There are also studies on the "mae geri" movement (forward kick) using the Vicon optical system (with twelve MX-13 cameras) to create pattern plots and perform statistical comparison among the five expert karatekas who performed the technique [76].…”
Section: Related Workmentioning
confidence: 99%